A Deep Analysis on Widely Used Condensation Route for Preparing Aminophosphines: Synthesis and Spectral Characterization of an Aminobis(chlorophosphine), (NC4H8N)[P(i-Pr2N)Cl]2. Issue 9 (1st September 2016) - Gopalakrishnan, Janarthanan
Abstract : Aminophosphines are useful as ligands and the most convenient method to synthesize is the condensation route that is straightforward, simple and easy to execute and get the products. Rx PClz (x = 0–2, y = 1–3) and amines are widely used as phosphorus and nitrogen substrates. Vast examples such as Phx (R2 N)y PClz [x < 3; y > 0; z < 3] are available in the literature which used condensation route. A deep analysis was carried out on this route and the author analyzes various parameters that affect product formation, purity, and yield. Using the optimized conditions, (NC4 H8 N)[P( i -Pr2 N)Cl]2 was prepared and spectrally characterized.